Emotions and mathematical activities integrated into a story in a three-year-old classroom (Edma 0-6: Educación Matemática en la Infancia, 2023)
This article is based on the teaching and learning of mathematics from the perspective of Realistic Mathematics Education and, by taking into account the current curriculum in Early Childhood Education, it emphasizes the importance of working on emotions together with mathematics from the early ages. The experience has been carried out with 17 boys and girls from the 1st year of Early Childhood Education. A tale elaborated especially to be able to establish relationships between emotions, the students' own feelings, and some mathematical concepts is used as a didactic instrument and common thread. The collected documentation allows the analysis of the actions of boys and girls, linking mathematical aspects and emotions. A progress in the development of their affectivity is attested, as well as an improvement in the development of mathematical logical thinking.
Keywords: Realistic Mathematics Education; Early Childhood Education; Tale; Affective domain; Didactic instrument; Curriculum guidelines